# how to write for loop for this case?

2 visualizaciones (últimos 30 días)
bahareh bshrt el 10 de Feb. de 2021
Respondida: Manash Sahoo el 10 de Feb. de 2021
I have this relation
deltaT=50;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T0+(deltaT*F_e);
T50=K_eff\F_eff;
deltaT=100;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T50+(deltaT*F_e);
T100=K_eff\F_eff;
deltaT=150;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T100+(deltaT*F_e);
T150=K_eff\F_eff;
can anyone help me to write code for this?(code for deltaT & Tn)
##### 0 comentariosMostrar -2 comentarios más antiguosOcultar -2 comentarios más antiguos

Iniciar sesión para comentar.

### Respuestas (1)

Manash Sahoo el 10 de Feb. de 2021
Could you elaborate on your question? Are you trying to execute this code in the context of a for loop? Additionally, I don't see a variable named "Tn".
But, if your question is how to turn this code into a for loop with 'deltaT' as the iterating variable, try this:
for deltaT = 0:50:150
if deltaT == 0
deltaT = 1;
end
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T0+(deltaT*F_e);
T50=K_eff\F_eff;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T50+(deltaT*F_e);
T100=K_eff\F_eff;
K_eff=C_E+(teta*deltaT*K_E);
F_eff=(C_E-((1-teta)*deltaT*K_E))*T100+(deltaT*F_e);
T150=K_eff\F_eff;
end
##### 0 comentariosMostrar -2 comentarios más antiguosOcultar -2 comentarios más antiguos

Iniciar sesión para comentar.

### Categorías

Más información sobre Loops and Conditional Statements en Help Center y File Exchange.

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by